Alih Kode dan Campur Kode dalam Lirik Lagu pada Album “Crows” Karya Rapper Miyachi - Kurniawan, Nandana Ardra; Djaya, Hermansyah; Saptaji, Hargo (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2025)
In sociolinguistic studies, the phenomenon of code switching and code mixing does not only occur in everyday conversation, but also in songs. This study aims to analyze code switching and code mixing in the song lyrics on Miyachi's album Crows. The method used is descriptive qualitative, where the results of the data analysis will be explained in more depth. The results of this study are, in this album there were 24 code switching events and 194 code mixing. Of the 194 code mixings, there are 136 words, 36 phrases, and 24 clauses. 187 are external code mixing and 7 are internal code mixing, and the cause of code switching and code mixing in this album is the songwriter who is a bilingual background